Non-Performing Financing and Islami Corporate Governance influence on Fraud in Sharia Commercial Banks - Chairunisa, Mariyam (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2024)
This study aims to examine impact of Non Performing Financing and Islamic Corporate Governance on Fraud on sharia Commercial Bank in Indonesia. The independent variables used in this study are first, Non-Performing Financing and secondly is Islamic Corporate Governance. While the dependent variable of this study is Fraud. The research method uses secondary data in the form of annual reports and good corporate governance reports of Islamic banks in Indonesia. The data obtained were processed by logistic regression analysis using SPSS statistical tools. The results showed a significant influence between Non Performing Financing on Fraud and insignificant influence between Islamic Corporate Governance with the proxy of the duties and authority of the Sharia supervisory board and audit committee on Fraud. Future studies are expected to test by adding other variables.